Grown ups 2 [videorecording (DVD)] - Sandler, Adam; Sandler, Adam; James, Kevin, 1965-; Rock, Chris; Spade, David; Hayek, Salma, 1966-; Rudolph, Maya; Bello, Maria, 1967-
Lenny has decided to relocate his family back to the small town to have his kids grow up where he and his friends grew up. This time around, the grownups are the ones learning lessons from their kids on a day notoriously full of surprises: the last day of school.